Motor imagery and action-observation in neurorehabilitation: A study protocol in Parkinson's disease patients - Rizzi, Beatrice; Nuresi, Christian; Rovacchi, Claudio; Bacchini, Massimo; Savi, Federica; Falco, Lucia; Schianchi, Luca; Scaglioni, Augusto; Ciracì, Chiara; Costantino, Cosimo; Buccino, Giovanni (Frontiers in Neurology, 2022)
Introduction: Action Observation Treatment (AOT) and Motor Imagery (MI) represent very promising cognitive strategies in neuro-rehabilitation. This study aims to compare the effectiveness of the two cognitive strategies, taken alone or combined, in Parkinson’s disease patients. Material and Methods: This study is designed as a prospective randomized controlled trial, with four arms. We estimated a sample size of 64 patients (16 in each treatment group) to be able to detect an effect size of F=0.4 with a statistical significance of 0.05. Primary outcomes will be functional gains in the FIM and UPDRS scales. Secondary outcome measure will be functional gain as revealed by kinematic parameters measured at Gait Analysis. Discussion: The results of this trial will provide insights into the use of AOT and MI, taken alone or combined, in the rehabilitation of Parkinson's disease patients. Ethics and dissemination: The study protocol was approved by the Ethics Committee of the Don Gnocchi Foundation. The study will be conducted in accordance with the 1996 World Medical Association guidelines and according to good clinical practice. The study has been registered on clinicaltrial.gov under the following code: AOTPRFDG. Dissemination will include both submission of the study to peer-reviewed journals and discussion of the study protocol at conferences.